Unveiling the Value of Pancasila Learning in Early Childhood: The Garuda Bird Puzzle Game Approach - Nursalim; Widodo, Agus; Pristiani, Yunita Dwi; Iswantiningtyas, Veny; Karisma, Dwi Yogi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
The cultivation of Pancasila values in early childhood is essential for shaping individuals with a strong national identity. However, current methods for instilling these values remain suboptimal. This study investigates the effectiveness of the Garuda Pancasila puzzle game in enhancing the internalization of Pancasila values among early childhood learners. Using a quasi-experimental nonequivalent control group design, the study involved 77 children aged 5–6 years from Perwanida I Kindergarten, Kediri City. Data were collected using observation sheets structured around the five fundamental values of Pancasila: (1) Belief in One God, (2) Just and Civilized Humanity, (3) Unity of Indonesia, (4) Democracy Led by Wisdom in Representative Deliberation, and (5) Social Justice for All Indonesians. The research instrument comprised 18 items rated on a binary scale (1 or 0). The findings indicate a significant improvement in the internalization of Pancasila values in the experimental group (mean score: 9.60) compared to the control group (mean score: 7.88) after implementing the Garuda puzzle game. The independent t-test results (t = -2.068, p = 0.042) confirm a statistically significant difference, underscoring the effectiveness of the game-based intervention. Additionally, children in the experimental group exhibited greater engagement, active participation, and improved social interactions, reinforcing both cognitive and socio-emotional development. The structured yet flexible nature of the game facilitated hands-on learning, enabling children to explore ethical reasoning and collaborative problem-solving. These results highlight the potential of play-based learning strategies in character education. The study recommends integrating culturally relevant games into early childhood curricula to strengthen civic awareness and national identity. Future research should examine longitudinal effects and explore the integration of digital puzzle games to assess long-term value internalization and broader scalability in diverse educational settings.